Comparative Analysis Of The Levels Of Effectiveness, Efficiency, And Independence Of Regional Financial Management After And Before Covid-19 (A Case Study Of Districts-Cities In South Sumatra Province) - Pratiwi, Isneni (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
The Covid-19 pandemic has had a significant impact on the economic sector, especially in the South Sumatra Province, which has caused a decline in regional financial income. This study aims to analyze the comparison of effectiveness, efficiency, and regional financial independence before and during the Covid-19 pandemic in districts/cities in South Sumatra Province. In this study, there were 17 district-city governments in South Sumatra Province which were sampled using the saturated sampling method. The data amounting to 34 for each variable before and during Covid-19. The analytical tool used in this study is the Difference Test. The results of this study indicate that there were significant differences in the effectiveness and efficiency of regional finance between before and during Covid-19. meanwhile.